Comparative estimations on carbon sequestration potential of selected urban trees in Kuching city - Siti Zubaidah, binti Mat Tahir. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Amelioration of global warming presents opportunities fo urban forests to play a critical role in helping combating the increasing CO2 level in the atmosphere. Trees act as a sink for CO2 through photosynthesis and storing excess carbon as biomass. Although some studies have been done on the structure and diversity of urban trees in Kuching City, Sarawak, no information are available concerning carbon storage and CO2 sequestration by urban trees. In order to estimate the carbon storage and sequestration potential, measurement of diameter size and tree height were conducted at selected locations as a representive sample.